India: decentralised planning themes and issues - Sanyal, B M (New Delhi Concept, 2001)
This book is an introduction to the general and basic elements of decentralised planning.The book concepts of micro level planning ,participation of local people has been discussed in reference to behavioural science approches.This volumes also covered th
Keywords: Political science-India; public administration-India; Decentralisation in government-India; Planning-India